Serum electrolyte balance and antioxidant status of broiler chickens fed diets containing varied levels of monosodium glutamate (MSG) - Olarotimi, Olumuyiwa Joseph (2021)
The results revealed that MSG inclusion above 0.75 g/kg diet significantly (P < 0.05) increased the serum Na+ and K+ concentrations of the broiler chickens when compared with birds on the control diet, whereas the serum Cl− concentration significantly (P < 0.05) decreased from 0.50 g MSG/kg diet inclusion level. On the other hand, MSG inclusion level above 0.50 g/kg diet increased the serum MDA concentration (from 2.60 ± 0.01 to 4.60 ± 0.00) of the birds while serum GSH-Px and T-AOC concentrations significantly (P < 0.05) reduced from 170 ± 0.28 to 120 ± 0.26 and 3.30 ± 0.01 to 1.70 ± 0.01, respectively.